The Political View of Muhammadiyah; Does It Closer to The Welfare State? - Angga Fajar Maulana (Universitas Muhammadiyah Malang, 2024)
This article discusses Muhammadiyah's political views in the context of the organization's relationship with the concept of the welfare state. As one of the largest Islamic organizations in Indonesia, Muhammadiyah has a significant role in political and social dynamics in this country. This study explores whether the values ​​and policies promoted by Muhammadiyah are closer to the principles of a welfare state, which emphasizes social equality, economic justice, and public services. Using a qualitative approach, this research analyzes various Muhammadiyah documents, policies, and official statements, as well as their historical and political context. The findings show that Muhammadiyah consistently encourages strengthening the role of the state in ensuring the welfare of society, while still maintaining Islamic principles and political independence. This study offers a new perspective on Muhammadiyah's contribution to realizing a just and civilized social order in Indonesia.